PROHIBITION OF SEGREGATION – A MISSING NORM IN INTERNATIONAL HUMAN RIGHTS LAW? - DE SILVA Monika (2018)
The aim of this paper is to answer whether and how international human rights law protects from segregationist policies – a still present phenomenon including such practices as prohibition of interfaith marriages, physical separation of men and women in everyday activities or segregation of Roma children in education. I firstly turn to conceptual problems regarding the term “segregation” by proposing its definition and categorizing its diverse displays. I draw a conclusion that segregation and discrimination are separate, although often intertwining, concepts. Subsequent parts of the paper contain an analysis of various international human rights law instruments conducted in search of a norm prohibiting segregation. I conclude that there is no explicit and general prohibition of segregation in international law, however some fragmentary and dispersed norms concerning segregation can be found through analysis of treaties, customary rules as well as doctrinal and judicial interpretations.